Jlab Chl1 2K Cold Box Replacement. Issue 1 (March 2020) - Yang, S; Dixon, K; Laverdure, N; Norton, R; Butler, C; MacDuffie, C; Rath, D; Brown, R; Thompson, S; Creel, J; Sprouse, R; Renzo, T; et al.
Abstract: A new sub-atmospheric cold box (SC1R), which hosts five technologically superior, water-cooled compressors and one similar 4K-2K refrigeration recovery heat exchanger, was proposed in July 2017, to replace the existing 2K cold box. The design of the new 2K cold box and the external support system have been completed. The project is in the fabrication and assembly phase, which will be completed at JLab. We present the design features, fabrication, installation and commissioning schedule for the new 2K cold box.